Proportional sway-based electrotactile feedback improves lateral standing balance - Raghav Hari Krishna, V. S.; Kim, Jeonghee; Chang, Shuo-Hsiu; Choe, Yoonsuck; Park, Hangue (Frontiers in Neuroscience, 2024)
Plantar cutaneous augmentation is a promising approach in balance rehabilitation by enhancing motion-dependent sensory feedback. The effect of plantar cutaneous augmentation on balance has been mainly investigated in its passive form (e.g., textured insole) or on lower-limb amputees. In this study, we tested the effect of plantar cutaneous augmentation on balance in its active form (i.e., electrical stimulation) on individuals with intact limbs. Ten healthy subjects participated in the study and were instructed to maintain their balance as long as possible on the balance board, with or without electrotactile feedback evoked on the medial side of the heel, synched with the lateral board sway. Electrotactile feedback was given in two different modes: 1) discrete-mode with stimulation on/off by a predefined threshold of lateral board sway and 2) proportional-mode with the stimulation frequency inversely proportional to the amount of lateral board sway. All subjects were distracted from the balancing task by the n-back counting task, to test subjects' balancing capability with minimal cognitive involvement. Proportional-mode E-stim, along with the n-back counting task, increased the balance time from 1.86±0.03 s to 1.98±0.04 s (p=0.010). However, discrete-mode E-stim did not change the balance time (p=0.669). These results suggest that proportional electrotactile feedback better mimics the natural tactile sensation of foot pressure than its discrete counterpart.